Patient-Specific Circulating Tumor DNA Detection during Neoadjuvant Chemotherapy in Triple-Negative Breast Cancer. (6th January 2020) - Riva, Francesca; Bidard, Francois-Clement; Houy, Alexandre; Saliou, Adrien; Madic, Jordan; Rampanou, Aurore; Hego, Caroline; Milder, Maud; Cottu, Paul; Sablin, Marie-Paule; Vincent-Salomon, Anne; Lantz, Olivier; et al.
Abstract: BACKGROUND: In nonmetastatic triple-negative breast cancer (TNBC) patients, we investigated whether circulating tumor DNA (ctDNA) detection can reflect the tumor response to neoadjuvant chemotherapy (NCT) and detect minimal residual disease after surgery. METHODS: Ten milliliters of plasma were collected at 4 time points: before NCT; after 1 cycle; before surgery; after surgery. Customized droplet digital PCR (ddPCR) assays were used to track tumor protein p53 ( TP53 ) mutations previously characterized in tumor tissue by massively parallel sequencing (MPS). RESULTS: Forty-six patients with nonmetastatic TNBC were enrolled. TP53 mutations were identified in 40 of them. Customized ddPCR probes were validated for 38 patients, with excellent correlation with MPS ( r = 0.99), specificity (≥2 droplets/assay), and sensitivity (at least 0.1%). At baseline, ctDNA was detected in 27/36 patients (75%). Its detection was associated with mitotic index ( P = 0.003), tumor grade ( P = 0.003), and stage ( P = 0.03). During treatment, we observed a drop of ctDNA levels in all patients but 1. No patient had detectable ctDNA after surgery. The patient with rising ctDNA levels experienced tumor progression during NCT. Pathological complete response (16/38 patients) was not correlated with ctDNA detection at any time point. ctDNA positivity after 1 cycle of NCT was correlated with shorter disease-free ( P < 0.001) and overall ( P = 0.006) survival. CONCLUSIONS: Customized ctDNA detection by ddPCR achieved a 75% detection rate at baseline. During NCT, ctDNA levels decreased quickly and minimal residual disease was not detected after surgery. However, a slow decrease of ctDNA level during NCT was strongly associated with shorter survival.